1974
DOI: 10.1346/ccmn.1974.0220112
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Absorption and X-Ray Diffraction Study of Butylammonium Complexes of Phyllosilicates

Abstract: Abstraet--I.R. absorption and X-ray diffraction data on butylammonium complexes of vermiculites show, when compared with the Wyoming montmorillonite complex, that the tetrahedral location of charge determines the keying of the -NH~ groups into the ditrigonal cavities and that these groups have their Ca axes perpendicular to the layers. The aliphatic chains adopt different conformations depending on the area available per exchange position; they will either: (a) adopt an 'all-trans' conformation with their axes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

1976
1976
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…The C-N bonds are steeply inclined to the silicate layers, and the nitrogen atoms are located over the centers of ditrigonal holes formed by the surface oxygen atoms. The average position for the nitrogen atom, at 4.78 A from the center of the octahedral sheet, is intermediate between that found by Johns and Sen Gupta (1967) in alkylammonium complexes with the Llano vermiculite and that found in a butyiammonium complex with vermiculite from Beni-Buxera, Spanish Morocco, by Martin-Rubi et al (1974). These two values were reported to be 4.65 and 4.85/~, respectively.…”
Section: Discussionmentioning
confidence: 46%
“…The C-N bonds are steeply inclined to the silicate layers, and the nitrogen atoms are located over the centers of ditrigonal holes formed by the surface oxygen atoms. The average position for the nitrogen atom, at 4.78 A from the center of the octahedral sheet, is intermediate between that found by Johns and Sen Gupta (1967) in alkylammonium complexes with the Llano vermiculite and that found in a butyiammonium complex with vermiculite from Beni-Buxera, Spanish Morocco, by Martin-Rubi et al (1974). These two values were reported to be 4.65 and 4.85/~, respectively.…”
Section: Discussionmentioning
confidence: 46%
“…In many cases ®llers such as glass beads, CaCO 3 or BaSO 4 , which have a very low aspect ratio, are employed. The mechanical properties may be widely improved by ®llers having a large aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…(2:1)-three layered silicate, such as montmorillonite or hectorite, are known as good nano®llers because they can be separated into single sheets with a thickness of approximately 1 nm. Large amounts of water can be loaded in the interlayer spacing or the Na + and Li + cations can be replaced with organic cations, for example, R-NH 3 [2±4]. A prerequisite to obtain a nanocomposite with highly improved properties is a ®ne dispersion on the exfoliated silicate layers [5±8].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of alkylammonium methodology has been provided by Lagaly (1994). When the charge on the 2:1 layer is tetrahedrally located, the combined effect of electrostatic and H-bond interactions determines the keying of the NH 3 groups of alkylammonium ions into the ditrigonal cavities (Martfn-Rubf et al 1974). A recent study of layer charge determination and alkylammonium ion-exchange technique is reported by Mermut (1993).…”
Section: Introductionmentioning
confidence: 99%